MR Linac radiotherapy : a new personalized treatment approach - Ozyar, Enis; Onal, Cem; Hackett, Sara L. (Advances in magnetic resonance technology and applications, 2022)
MR Linac Radiotherapy: A New Personalized Treatment Approach comprises both clinical and physical aspects of this new technology. The book covers treatment planning, workflow and technical issues about MR-Linac. Specially, the clinical use of MR-Linac according to different cancer types is presented by experienced physicians. This is a unique guide for medical physicists, RTTs, dosimetrists and physicians, as well as radiation oncologists and their teams. The MR Linac combines two technologies - a magnetic resonance imaging scanner and a linear accelerator - to precisely locate tumors, tailor the shape of radiation beams in real-time, and precisely deliver doses of radiation, even to moving tumors. This highly innovative technology is very new, and the number of newly installed MR-Linac machines will gradually increase worldwide. However, as there is no published book as a guideline, this book will help new MR-Linac users and centers planning to have MR-Linac.